Factors influencing visitors' evaluation of service quality in Giant Panda Conservation Centre (GPCC), Zoo Negara - Yee, Lai Ling; Ramachandran, Sridar; Shuib, Ahmad; Johari, Shazali; Mohammad Afandi, Syamsul Herman (Universiti Malaysia Sarawak, 2018)
Giant Panda Conservation Centre (GPCC) was built at the amount of RM 25 million, with the purpose to house giant pandas, which were loaned from China, a gesture to commemorate 40 years diplomatic of ties between China and Malaysia. However, service quality of GPCC has yet to be determined, even though the centre has received many visitors since its establishment in 2014. In addition, GPCC management has no direction to enhance its service quality. Therefore, this study was conducted to determine the visitors’ satisfaction towards service quality at the GPCC, as well to uncover factors which influence it. The SERVPERF model was adopted in this study by using a four-point Likert Scale as the measurement. By using the Statistical Package for the Social Sciences (SPSS), the results showed that generally, visitors were satisfied with the service quality of GPCC. This was probably because GPCC provided their best service for visitors. Besides, regression analysis revealed that visitors’ re-visit intentions, recommendation intentions, religion, age, and sources of information were factors that influenced visitors’ satisfaction. In short, subsequent and effective steps should be taken by the management to enhance service quality in GPCC.